Besieged bedfellows: Israel and the land of apartheid - Joseph, Benjamin M. (New York, 1988)
The several books that deal with the relationship between Israel and South Africa, this is the most scholarly and sophisticated. Joseph argues that the relationship took a long time to evolve and that it rests on a community of interests and complementary resources. Most important, as the world's two remaining political systems committed to separatist philosophies that exclude indigenous Third World majorities, they have developed an underlying sense of solidarity and kinship. . . . [T]his is a valuable and solid contribution to an understanding of what is widely held to be a highly anomolous relationship. Choice A provocative look at the surprisingly close relationship between Israel and South Africa. Besieged Bedfellows draws on a wealth of Western, South African, Israeli sources, including materials previously published only in Hebrew. The book examines the commercial and military spheres of this relationship as well as the available information on Israeli-South African nuclear cooperation. A seperate chapter addresses the familiar objection, Everyone does it [business with South Africa]--why focus on Israel? The book next gives a profile of South African Jewry and what, if any, role this community might have played in forging the connection. Besieged Bedfellows goes on to present a compelling case that there is a great deal more to the Israeli-South African relationship than expediency and realpolitik. The author demonstrates that as well as conducting business, South African whites and Israelis have shown a considerable amount of solidarity and understanding towards each other. He then carefully examines the backgrounds and ruling ideologies of these two political groups.